2022
DOI: 10.1155/2022/8432360
|View full text |Cite|
|
Sign up to set email alerts
|

Different Associated Aspects That Influence Complication Rates on Clinical PKP Surgery Using Smart Medical Big Data

Abstract: Osteoporotic vertebral compression fractures are on the rise in modern society due to the aging population, and this often results in painful symptoms and kyphotic abnormalities in patients. Bone cement was injected into the vertebral body to reinforce the vertebral body and restore most of the damaged vertebrae’s natural height. Percutaneous kyphoplasty is the name given to this type of procedure (PKP). Bone cement leakage has been linked to several problems, according to the research. Neurological problems m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%